EPISTEMOLOGI SUFI DAN TANGGUNG JAWAB ILMIAH - Nur, Syaifan (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
A Characteristic of sufi knowledge or epistemology based on intuition and reality of thespiritual world that only could beexperienced by sufis. This distinctive mode of epistemology invited numerous questions, especially for those who were influenced by empiricalpositivistic points of view. How it could be and how is it scientifi cally responsible. For them, this mode of knowledge is assumed as â€œunrealâ€, and is impossible to being scientific, let alone objectively recognized for its reliability. This article attempts to respond to that challenge or perhaps â€œaccusationâ€, whilestressing the point on two aspects: fi rst,exposition of characteristics of sufi epistemology that seem so diff erent from Western mode of epistemology (rationalism or empiricism), and second, trying to rationalize the reality of sufi spiritualexperiences as being scientifi cally responsible.